Effects of vitamin D3 stimulation of thioredoxin‐interacting protein in hepatocellular carcinoma. Issue 13 (25th March 2014) - Hamilton, James P.; Potter, James J.; Koganti, Lahari; Meltzer, Stephen J.; Mezey, Esteban
Abstract : Aim: Thioredoxin‐interacting protein (TXNIP) promotes oxidative stress by inactivating thioredoxin (TXN). This protein is involved in diverse disease processes, including insulin resistance, atherosclerosis and carcinogenesis. The aim of the present study was to measure the expression and function of TXNIP in in vitro models of liver disease, as well as in primary human hepatocellular carcinoma (HCC) tissue specimens. In addition, we wanted to determine the effects of vitamin D3‐induced TXNIP stimulation in HCC‐derived cell lines. Methods: TXNIP expression was measured by quantitative reverse transcription polymerase chain reaction and western blots. TXNIP expression was stimulated by vitamin D exposure and by transfection. Cell proliferation, apoptosis and reactive oxygen species were determined by standard assays. Results: TXNIP expression levels were low in HCC cell lines, and vitamin D3 stimulated TXNIP expression in vitro. In HCC cells transfected with a TXNIP expression vector or treated with exogenous vitamin D3, there was a reduction in cell proliferation and an increase in apoptosis. Cells expressing TXNIP were markedly susceptible to oxidative injury induced by cobalt chloride or bacterial lipopolysaccharide. TXNIP expression was reduced or absent in a majority of primary human HCC specimens relative to matching, non‐cancerous liver tissue. Conclusion: TXNIP expression is low or absent in human HCC specimens and HCC‐derived cell lines. Vitamin D3 stimulates TXNIP expression, resulting in diminished proliferation and enhanced apoptosis. Liver cells expressing TXNIP are primed for oxidative injury. These findings suggest that stimulation of TXNIP expression, by factors such as vitamin D3, may attenuate carcinogenesis in patients with chronic liver disease.